MiR-214 Attenuates the Osteogenic Effects of Mechanical Loading on Osteoblasts - Yuan, Yu; Guo, Jianmin; Zhang, Lingli; Tong, Xiaoyang; Zhang, Shihua; Zhou, Xuchang; Zhang, Miao; Chen, Xi; Lei, Le; Li, Hui; Liu, Timon Cheng Yi; Xu, Jiake; Zou, Jun (International Journal of Sports Medicine, 2019)
Exercise is an effective way to prevent osteoporosis, but its mechanism remains unclear. MicroRNAs (miRNAs) play an essential role in bone metabolism. Recently, mechanical loading was reported to induce changes in miRNA expression in osteoblasts. However, the role of miRNAs in bone under exercise and its underlining mechanisms of action still remain unknown. MiR-214 was reported to regulate the process of osteogenesis and is considered a biomarker of osteoporosis. In this study, we aimed to investigate whether exercise could induce changes in miRNA expression in bone and to study the effects of miR-214 on mechanical loading-induced osteogenesis in osteoblasts. The results showed that miR-214 was down-regulated in both tibia from C57BL/6 mice after exercise in vivo and in osteoblasts after mechanical strain in vitro. Mechanical strain could enhance the ALP activity, promote matrix mineralization, up-regulate the expression of osteogenic factors such as ATF4, Osterix, ALP and β-catenin, and down-regulate RANKL and RANK expression. Over-expression of miR-214 not only inhibited the expression of these osteogenic factors but also attenuated mechanical strain-enhanced osteogenesis in osteoblasts. Collectively, our results indicated that miR-214 could attenuate the osteogenic effects of mechanical loading on osteoblasts, suggesting that inhibition of miR-214 may be one of the ways in which exercise prevents osteoporosis.
Keywords: exercise; mechanical strain; miR-214; osteoblasts; osteoporosis